Resilient Risk Management Model of Sustainable Smart Cities - Das, Munmun (Digital Repository of Theses - SSBM Geneva, 2025)
Smart city risk management has emerged as a crucial area of focus in response to growing challenges in today’s world. Environmental issues, global pandemics, and geopolitical instability have compelled more people to migrate to urban areas in search of safety, better healthcare, food security, education, and employment opportunities. While cities offer these benefits, they also bring about new risks and operational challenges. This research addresses those risks, focusing specifically on supply chain management and corporate finance, two critical sectors that sustain the backbone of smart cities. The study aligns with global Sustainable Development Goals (SDGs), emphasizing the use of advanced technologies like Artificial Intelligence (AI), Internet of Things (IoT), and Blockchain to build resilient urban systems. A mixed-methods approach was used to explore these sectors. Quantitative data was gathered through a 40-question survey conducted over three months with urban professionals such as supply chain experts, educators, and corporate leaders. Qualitative insights were collected through hands-on prototype testing with stakeholders like ERP consultants, CFOs, and intercompany accountants. Key challenges identified include demand-supply misalignment, high transportation costs, fragmented distribution channels, inefficiencies in inventory management, and the complexities of cross-border intercompany reconciliation. Additionally, the lack of unified digital platforms across multiple entities in the ecosystem increases operational risks. To tackle these issues, the research led to the development of innovative solutions. Swikriti, a blockchain-based supply-chain management solution with inbuilt quality control and certification platform, and ensures product integrity. It also delivers real time analytics predictions and dashboard, Digital Twin & simulations which facilitates in optimum decision making. Viniyog focuses on automating intercompany reconciliations, mitigating disputes, and improving financial transparency globally. Both the solutions address major sustainable development goals (SDGs) like Decent Work and Economic Growth (Goal 8), Industry, Innovation, and Infrastructure (Goal 9), Reduced Inequalities (Goal 10), Responsible Consumption and Production (Goal 12), Climate Action (Goal 13). The outcomes of this research highlight the transformative potential of deep-tech solutions in mitigating urban risks. By addressing these pressing challenges, this study contributes significantly to sustainable smart city innovation. The study offers a pathway for cities to operate more efficiently and equitably in the future. It also sets the foundation for further studies on technology adoption across different urban sectors and demographics.